2012
DOI: 10.1289/ehp.1205014
|View full text |Cite
|
Sign up to set email alerts
|

Rice Consumption and Urinary Arsenic Concentrations in U.S. Children

Abstract: Background: In adult populations, emerging evidence indicates that humans are exposed to arsenic by ingestion of contaminated foods such as rice, grains, and juice; yet little is known about arsenic exposure among children.Objectives: Our goal was to determine whether rice consumption contributes to arsenic exposure in U.S. children.Methods: We used data from the nationally representative National Health and Nutrition Examination Survey (NHANES) to examine the relationship between rice consumption (measured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
119
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(127 citation statements)
references
References 60 publications
6
119
0
Order By: Relevance
“…Collecting more detail on the type of fish consumed would be a useful addition to future studies of mercury to enhance exposure assessment. More specific questions such as how often the participants eat fish known to have higher levels of mercury could be included in future questionnaires; for example, shark, marlin, swordfish and tuna are known to contain higher levels of mercury than other fish (Davis et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Collecting more detail on the type of fish consumed would be a useful addition to future studies of mercury to enhance exposure assessment. More specific questions such as how often the participants eat fish known to have higher levels of mercury could be included in future questionnaires; for example, shark, marlin, swordfish and tuna are known to contain higher levels of mercury than other fish (Davis et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proved that arsenic can easily cross the placental barrier to the fetus [11] and even moderate exposure to arsenic during pregnancy and early life is linked with various adverse health outcomes, including neurological problems in the fetus [12,13] and children's [14,15]. Further, the various human population-based studies found that arsenic concentrations in urine were inversely associated with Verbal IQ, Performance IQ and processing speed problems in children's [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…It would thus be misleading to summarize just one of the models, as this could foster a false sense of certainty. Yet scientific articles often [2,3,4,5,6]. By paying attention to issues of model selection, professional communities can guard against publication bias (see [7]) and reduce the prevalence of contradictory claims within scientific literature.…”
Section: Introductionmentioning
confidence: 99%